Terahertz transmission through rings of quantum dots-nanogap. (27th January 2016) - Tripathi, Laxmi-Narayan; Bahk, Young-Mi; Choi, Geunchang; Han, Sanghoon; Park, Namkyoo; Kim, Dai-Sik
Abstract: We report resonant funneling of terahertz (THz) waves through (9 ± 1) nm wide quantum dots-nanogap of cadmium selenide quantum dots silver nanogap metamaterials. We observed a giant THz intensity enhancement (∼10 4 ) through the quantum dots-nanogap at the resonant frequency. We, further report the experimentally measured effective mode indices for these metamaterials. A finite difference time domain simulation of the nanogap enabled by the quantum dots supports the experimentally measured THz intensity enhancement across the nanogap. We propose that these low effective mode index terahertz resonators will be useful as bio/chemical sensors, gain-enhanced antennas, and wave guides.